Effect of V2O5 addition on the structural and magnetic properties of Ni–Co–Zn ferrites - M Samir Ullah; M Firoz Uddin; A A Momin; M A Hakim (Materials Research Express, 2021)
The effect of V _2 O _5 addition on the structural and magnetic properties of Ni–Co–Zn ferrites having the compositions Ni _0.62 Co _0.03 Zn _0.35 Fe _2 O _4  + xV _2 O _5 (where x = 0.0, 0.5, 1.0 and 1.5 wt%) are reported. The samples were prepared by solid state reaction. The crystalline structure of all the samples showed cubic spinel structure. The microstructural study reveals that the grain growths of Ni–Co–Zn mixed ferrites are strongly depended on the amount of V _2 O _5 contents. The saturation magnetization and coercivity were determined from the magnetic hysteresis loops, while Curie temperatures were estimated from the temperature dependence of magnetization. The saturation magnetization almost linearly decreased from 77 emu g ^−1 for x = 0.0 wt% V _2 O _5 to 56 emu g ^−1 for x = 1.5 wt% V _2 O _5 . Curie temperatures for the studied samples decreased with increase of V _2 O _5 addition. A general termed of permeability enhancement is clearly evidenced on V _2 O _5 addition.